Modification of the AODV Routing Discovery Mechanism in Wireless Mesh Networks - Alameri, Ibrahim Ahmed Salman (Univerzita Pardubice, 2024)
This thesis offers a comprehensive analysis of Wireless Mesh Networks (WMNs), crucial in the evolution of advanced wireless technologies like Wireless Sensor Networks, the Internet of Things, and the Internet of Vehicles. It highlights WMNs? unique characteristics, such as self-configuration and scalability, while addressing their dynamic nature, posing challenges for routing protocols. The thesis explores the limitations of the Ad hoc On-Demand Distance Vector (AODV) protocol and introduces the Fuzzy Control Energy Efficient (FCEE) routing protocol as a solution. FCEE, integrating fuzzy logic with AODV, enhances network efficiency and longevity, demonstrating superiority over traditional protocols in terms of throughput, energy efficiency, and quality of service metrics. This work stands out for its innovative approach to applying informatics principles to wireless communications, mainly designing adaptive routing lutions for WMNs. This thesis effectively demonstrates the FCEE protocol?s advantages through rigorous simulations, showing its potential to improve link stability and network performance. This thesis is significant for its contribution to the field of wireless communications and Applied Informatics, offering a novel perspective on tackling routing challenges in WMNs and highlighting the importance of data-driven decision-making in modern networking environments. It sets a precedent for future research at the intersection of networking and informatics.
Keywords: bezdrátová mesh síť; směrovací protokoly; vývoj protokolu; FCEE; fuzzy logika; wireless mesh network; routing protocols; protocol evolution; FCEE; fuzzy logic